Precision farming: what do Italian farmers really think? An application of the Q methodology. (August 2022) - Vecchio, Yari; Di Pasquale, Jorgelina; Del Giudice, Teresa; Pauselli, Gregorio; Masi, Margherita; Adinolfi, Felice
Abstract: CONTEXT: Precision farming (PF) is a term that is now widespread throughout agricultural systems worldwide. It is studied in many ways, from its strictly technical connotation of a farm management strategy that uses information technology to support decision-making processes to the steppingstones and the dissection of the factors involved in the complex scenario of adopting related tools. Starting from the statement " In my opinion, precision farming is… ", the present work investigates the perspective of the agricultural entrepreneur in conceptualising PF. Some researchers have highlighted the role of the sphere of the self in adoption, but few efforts have been made to better understand the role played by farmers' perceptions in the formation of their thinking about innovative tools. OBJECTIVE: This work aims to deepen the sphere of the self and, in particular, the role played by farmers' perceptions when faced with the innovation adoption choice. The study presents a new conceptual framework identifying key stages for analysing adoption processes, focusing on the relationships between behaviour, structural dimensions and adoption, interpreted from the farmer perspective. METHODS: The Q methodology (QM) was used with a targeted sample of 23 farmers to identify prevailing discourses. In the first step, the socio-structural dimensions were analysed through descriptive analysis, and in the second step, the discourses were extracted by an intercorrelation matrix through the centroid procedure, translating the solution using varimax rotation. RESULTS AND CONCLUSIONS: This paper highlights that the QM is an appropriate technique for exploring and studying farmers' attitudes when challenged with innovation. The results reveal discourses that summarise three macro perspectives: the "proactive approach", which represents farmers who perceive PF as having a key role for agricultural enterprises; the "conservative approach", which characterises those who distrust innovations; and the "doubtful approach", which is the more sceptical vision. SIGNIFICANCE: This study demonstrates the importance of moving beyond simply quantitative studies that methodically analyse adoption processes and overcoming the constraints of qualitative research by employing a mixed approach to identify the common perspectives of farmers. This analysis can be used by policy makers as a new survey tool to make stakeholder consultations more effective, as the 3 approaches may help to enrich the discourse on PF. The results provide new perspectives to promote responsible policies to support the effectiveness of PF. Graphical abstract: Unlabelled Image Highlights: Few efforts were made to better understand the role played by the farmers' perception in the adoption of innovation. The Q methodology is used to study the perspectives on innovation in agriculture. Different perceptions about innovation reflect the context in which farmers operate. Understanding farmers' views can be useful for the policy network.